2016
DOI: 10.3389/fpsyg.2016.01248
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Support as a Social Resource in Educational Services: Construct Validity and Measurement Invariance of the User-Initiated Support Scale (UISS)

Abstract: Social support is an important resource for reducing the risks of stress and burnout at work. It seems to be particularly helpful for educational and social professionals. The constant and intense relationships with users that characterize this kind of service can be very demanding, increasing stress and leading to burnout. While significant attention has been paid to supervisors and colleagues in the literature, users have rarely been considered as possible sources of social support. The only exception is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 54 publications
1
16
0
3
Order By: Relevance
“…Considering occupational psychological health in the conceptual frame of the JD-R model [7, 25], only demands and resources related to job content and relations inside the organization are traditionally considered—even for professionals and academics [6] who spend a considerable part of their activities relating with users. External users are sometimes considered sources of requests [18, 24] but are much more rarely considered sources of social support [27, 28]. Moreover, the present study showed the relevance of the positive side of the academic-student relationship.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Considering occupational psychological health in the conceptual frame of the JD-R model [7, 25], only demands and resources related to job content and relations inside the organization are traditionally considered—even for professionals and academics [6] who spend a considerable part of their activities relating with users. External users are sometimes considered sources of requests [18, 24] but are much more rarely considered sources of social support [27, 28]. Moreover, the present study showed the relevance of the positive side of the academic-student relationship.…”
Section: Discussionmentioning
confidence: 60%
“…More precisely, the scale evaluates whether academics feel that their work is appreciated and recognized by the students.Students' excessive demands were measured using four items adapted from the excessive customer expectations dimension of the Customer-Related Social Stressors (CSS) scale [9] (e.g., students make excessive demands. ).Students' support was measured using four items adapted from the User-Initiated Support Scale (UISS) [28] (e.g., students explicitly appreciate my way of working. ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, JR could reduce the negative impact of JD on stress and burnout. For example, social support or autonomy [38,39] could moderate the impact of JD on job stress and burnout, while meaningfulness of work [40], autonomy [41,42] or social support [40,[42][43][44][45] could protect the ability to work, buffer strain or sustain work engagement.…”
Section: The Job Demands-resources Model Burnout and Work Engagementmentioning
confidence: 99%